The diagnostic accuracy of ascitic calprotectin for the early diagnosis of spontaneous bacterial peritonitis: systematic review and meta-analysis - Hadjivasilis, Alexandros; Tzanis, Alexander; Ioakim, Kalliopi J; Poupoutsi, Ioanna; Agouridis, Aris P.; Kouis, Panayiotis (My University, 2021)
Spontaneous bacterial peritonitis (SBP) is a common complication in patients with cirrhosis and has an incidence of up to 30% in hospitalized patients. Importantly, it may raise their mortality rate up to 30%. Hence, a delayed diagnosis is associated with poor prognosis. This systematic review aims to assess the diagnostic accuracy of ascitic fluid calprotectin for the early diagnosis of SBP in patients with ascites. This study was conducted in accordance with the PRISMA statement. A systematic literature search was conducted from inception to February 2020 in the following electronic bibliographic databases: MEDLINE, Scopus, The Cochrane Library and OpenGrey. Quality Assessment of Diagnostic Accuracy Studies tool was used to assess risk of bias. Ten studies were included in the qualitative and quantitative synthesis. Hierarchical summary receiver operating characteristic curves were plotted and the summary sensitivity of a positive ascitic fluid calprotectin assessment to detect SBP was 93% [95% confidence interval (CI) 90-95%] while the summary specificity was 89% (95% CI 80-95%), irrespectively of the method used. The positive likelihood ratio and negative likelihood ratio of the test were 8.7 (95% CI 4.4-17.1) and 0.08 (85% CI 0.06-0.12). All studies showed positive correlation between ascitic calprotectin and polymorphonuclear (PMN) leukocyte count. Ascitic calprotectin appears to be an excellent alternative to PMN leucocyte count of ≥250 cells/mm3 for the diagnosis of SBP with much faster time to diagnosis. Owing to its substantially high negative predictive value, the test can accurately exclude SBP avoiding unnecessary antibiotics in suspected patients.
Keywords: Calprotectin; Diagnosis; Diagnostic accuracy test; Spontaneous bacterial peritonitis